Determine the Outcome of Radical Cystectomy in the Management of Muscle Invasive Bladder Tumor (Medical Forum Monthly, 2024)
Objectives: To determine the outcome of radical cystectomy in the management of muscle invasive bladder tumor.Study Design: Observational / descriptive studyPlace and Duration of Study: This study was conducted at the Urology Wards 14, Liaquat University Hospital, Jamshoro from March 2007 to February 2009.Materials and Methods: 25 cases were studies through data collected by performa filled by each case separately. Base line Investigations like CBC, Urine DR, Blood Urea, Serum Creatinine, Serum Electrolytes, LFT, Clotting profile, serum total protein AG ration, Hepatitis B and C with Specific Investigations such as Ultrasound abdomen & pelvis, Contras CT abdomen Pelvis. Cystoscopy & biopsy under GA, Start irrigation by 7 days twice daily by 30 cc N/S till discharge. Ascending pouchogram for suspicious cases by 19 day. Remove of urethral catheter by 20th day. After discharge patient call for follow up. Post-operative was observing postoperative complication like survival, leakage, sepsis and bleeding.Results: In the present study predominantly 25 male patients with mean age of 70 ± 10 having 07 patients were died within 24 hrs. After surgery, 05 patients have postoperative bleeding and 02 patients have anatomotic leakage..Conclusion: The study concludes that more cases are required for justification of radical cystectomy in muscle invasive locally advance bladder tumor..